Will morphing boron-based inhibitors beat the β-lactamases? - Krajnc, A; Lang, P; Panduwawala, T; Brem, J; Schofield, C (Elsevier, 2019)
The β-lactams remain the most important antibacterials, but their use is increasingly compromised by resistance, importantly by β-lactamases. Although β-lactam and non-β-lactam inhibitors forming stable acyl-enzyme complexes with nucleophilic serine β-lactamases (SBLs) are widely used, these are increasingly susceptible to evolved SBLs and do not inhibit metallo-β-lactamases (MBLs). Boronic acids and boronate esters, especially cyclic ones, can potently inhibit both SBLs and MBLs. Vaborbactam, a monocyclic boronate, is approved for clinical use, but its β-lactamase coverage is limited. Bicyclic boronates rapidly react with SBLs and MBLs forming stable enzyme-inhibitor complexes that mimic the common anionic high-energy tetrahedral intermediates in SBL/MBL catalysis, as revealed by crystallography. The ability of boronic acids to 'morph' between sp2 and sp3 hybridisation states may help enable potent inhibition. There is limited structure-activity relationship information on the (bi)cyclic boronate inhibitors compared to β-lactams, hence scope for creativity towards new boron-based β-lactamase inhibitors/antibacterials.